ANALISIS PENGARUHINTELLECTUAL CAPITAL DAN STRUKTUR MODAL TERHADAP KINERJA KEUANGAN PERUSAHAAN PENERIMA PENGHARGAAN INDONESIAN MAKE STUDY TAHUN 2011-2014 - YANWARI, RONI (Jurnal Akuntansi AKUNESA, 2015)
The purpose of this study was to analyze the relationship and the influence of Value Added Intellectual coëficient (VAIC) and Structure of capital as measured by Debt to Equity Ratio (DER) at the company's financial performance award-winning Indonesian MAKE Study on financial performance as measured by ROE. IC analysis and structure aims to provide inputs for financial managers to improve financial performance through investing Intellectual Capital and efficient capital structure management. The data used in this study were taken from the 12 award-winning companies in Indonesia Indonesian MAKE Study during 2011-2014. This empirical study using purposive sampling technique and linear regression analysis results indicate that the Intellectual coëficient no significant negative effect and Debt to Equity is not significant positive effect on the financial performance of the company. Keywords: Intellectual Capital, Value Added Intellectual coëficient (VAIC), Capital Structure, Debt to Equty Ratio (DER), ROE, and Indonesian MAKE Study.